2005
DOI: 10.1007/s10549-005-0450-4
|View full text |Cite
|
Sign up to set email alerts
|

Tat mammaglobin fusion protein transduced dendritic cells stimulate mammaglobin-specific CD4 and CD8 T cells

Abstract: Proteins can be efficiently introduced into cells when fused to a protein transduction domain, such as Tat from the human immunodeficiency virus. We recently reported that dendritic cells transduced with a Tat fusion protein containing the extracellular domain of Her2/neu (Tat-Her2/neu) induced CD8 cytotoxic T lymphocytes (CTL) that specifically lysed Her2/neu-expressing breast and ovarian cancer cells. In the current study we further investigated the mechanism of protein transduction, utilizing the breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…4), consistent with the high in vitro pMHC presentation. Our results were in agreement with many studies, which reported that transduction of mDCs with recombinant fusion proteins containing HIV-Tat was preferential over transduction of iDCs [8,12,13]. The longevity of pMHC on the surface of mDCs might be an advantage of pulsing Ag to DCs after their maturation [27,28].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…4), consistent with the high in vitro pMHC presentation. Our results were in agreement with many studies, which reported that transduction of mDCs with recombinant fusion proteins containing HIV-Tat was preferential over transduction of iDCs [8,12,13]. The longevity of pMHC on the surface of mDCs might be an advantage of pulsing Ag to DCs after their maturation [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…This pathway is currently called "cross-presentation" pathway [4,21]. In an attempt to enhance the cellular uptake and promote the cross-presentation pathway in DCs, many investigators perused the recombinant fusion protein or synthetic peptides which contain CPPs tandemly linked to the Ag [7][8][9][10][11][12][13][14]. However the construction of such a recombinant proteins/ peptides are specific for a single Ag, limiting the usefulness of this technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant proteins, peptides, viral vectors, RNA, immune complexes and killed tumour cell lysates have been used in this capacity [5], among which the use of the protein transduction domain (PTD) has been given much attention, because it is safer than viral vectors yet equally effective in loading MUC1 [8,9]. It has been hypothesized that the intracellular delivery of tumour-associated antigens (TAAs) into mature DCs by a PTD, such as the human immunodeficiency virus (HIV) Tat peptide, allows DCs to process and present the internalized antigens to T cells by major histocompatibility complex (MHC) class I and II molecules efficiently [10,11]. DCs that are pulsed with Tat-TAA have been demonstrated to induce antigen-specific CD4 T cells effectively as well as cytotoxic T lymphocytes (CTLs) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that the intracellular delivery of tumour-associated antigens (TAAs) into mature DCs by a PTD, such as the human immunodeficiency virus (HIV) Tat peptide, allows DCs to process and present the internalized antigens to T cells by major histocompatibility complex (MHC) class I and II molecules efficiently [10,11]. DCs that are pulsed with Tat-TAA have been demonstrated to induce antigen-specific CD4 T cells effectively as well as cytotoxic T lymphocytes (CTLs) [11,12].…”
Section: Introductionmentioning
confidence: 99%